(18)O Labeling over a Coffee Break: A Rapid Strategy for Quantitative Proteomics - Mirza, Shama P. (2008)
Proteomics-based quantification methods for differential protein expression measurements are among the most important and challenging techniques in the field of mass spectrometry. Though numerous quantification methods have been established, no method meets all the demands for measuring accurate protein expression levels. Of the various relative quantification methods by isotopic labeling, (18)O labeling method has been shown to be simple, specific, cost-effective and applicable to a wide range of analyses. However, some researchers refrain from using the method due to long incubation periods required during the labeling process. To address this problem, we demonstrate a method by which the labeling procedure can be completed in 15 min. We digested and labeled samples using immobilized trypsin on micro-spin columns to speed up the enzyme-mediated oxygen substitution, thereby completing the labeling process within 15 min with high labeling efficiency. We demonstrate the efficiency and accuracy of the method using a four protein mixture and whole cell lysate from rat vascular endothelial cells.